Delineation of Ehlers–Danlos syndrome phenotype due to the c.934C>T, p.(Arg312Cys) mutation in COL1A1: Report on a three‐generation family without cardiovascular events, and literature review. Issue 2 (7th November 2016) - Colombi, Marina; Dordoni, Chiara; Venturini, Marina; Zanca, Arianna; Calzavara‐Pinton, Piergiacomo; Ritelli, Marco
Abstract : Classical Ehlers–Danlos syndrome (cEDS) is a rare connective tissue disorder primarily characterized by hyperextensible skin, defective wound healing, abnormal scars, easy bruising, and generalized joint hypermobility; arterial dissections are rarely observed. Mutations in COL5A1 and COL5A2 encoding type V collagen account for more than 90% of the patients so far characterized. In addition, cEDS phenotype was reported in a small number of patients carrying the c.934C>T mutation in COL1A1 that results in an uncommon substitution of a non‐glycine residue in one Gly‐Xaa‐Yaa repeat of the pro‐α1(I)‐chain p.(Arg312Cys), which leads to disturbed collagen fibrillogenesis due to delayed removal of the type I procollagen N‐propeptide. This specific mutation has been associated with propensity to arterial rupture in early adulthood; indeed, in literature the individuals harboring this mutation are also referred to as "(classic) vascular‐like" EDS patients. Herein, we describe a three‐generation cEDS family with six adults carrying the p.(Arg312Cys) substitution, which show a variable and prevalent cutaneous involvement without any major vascular event. These data, together with those available in literature, suggest that vascular events are not a diagnostic handle to differentiate patients with the p.(Arg312Cys) COL1A1 mutation from those with COL5A1 and COL5A2 defects, and highlight that during the diagnostic process the presence of at least the p.(Arg312Cys) substitution in COL1A1 should be investigated in cEDS patients without type V collagen mutations. Nevertheless, for these patients, as well as for those affected with cEDS, a periodical vascular surveillance should be carried out together with cardiovascular risk factors monitoring. © 2016 Wiley Periodicals, Inc.